Preparing for advanced practice radiation therapy in South Africa: Conceptual and curricular considerations - Oupa S. Motshweneng; Sibusiso Mdletshe (AOSIS, 2021)
The higher education landscape in South Africa has recently changed with the new National Qualifications Framework, leading to the introduction of four-year degrees in all four radiography disciplines. Additionally, there have been developments in the extension of roles in radiography, while the need for interdisciplinary practice has also been emphasised. The Professional Board for Radiography and Clinical Technology (PBRCT) of the Health Professions Council of South Africa is currently revising the scope of the profession which will now include extended roles. However, the extended role concept in radiation therapy has not received the attention similar to Diagnostic/Medical Imaging. The aim of this paper is, therefore, to provide concept clarification and key considerations for developing a postgraduate curricular framework for training radiation therapists to practise in the envisaged extended roles. For this narrative review, a Boolean search for advanced practice and role extension in radiation therapy was done on all databases (43) available on EbscoHost to source for peer-reviewed articles published between January 1950 and September 2020. A total of 17 articles met the inclusion criteria and were used to frame the discussion. Advanced practice emerged as the more suitable concept as it goes beyond an extension of tasks to include critical characteristics that are necessary to drive transformation in the local social, professional and educational arenas. It is envisaged that some of the key points discussed in this paper could assist the PBRCT in thinking about the implementation of the proposed extended roles for radiation therapists in South Africa.